Nitriding of chromium-nickel alloys synthesized by laser melting - Chudina O.V.; Zorin V.A. (E3S Web of Conferences, 2023)
The effect of nitriding on the structure and hardness of chromium-nickel alloy obtained by selective laser melting has been studied. It has been shown that after nitriding a weakly developed ε-phase nitride zone with a thickness of about 10 μm and an internal nitriding zone with a thickness of more than 300 μm are formed on the surface of the alloy, which is twice as much as that of nitrided similar alloys obtained by the conventional method. The microhardness of the nitrided layer is 3500 MPa, this is 1.5 times higher than the hardness of the core, so nitriding of powder materials produced by additive technologies can be recommended for surface hardening of parts operating under conditions of wear and cyclic loads.